BACTERIAL MUTATION; TYPES, MECHANISMS AND MUTANT DETECTION METHODS: A REVIEW - Mohammad B. Habibi Najafi; Parnian Pezeshki (European Scientific Journal, ESJ, 2014)
Mutation is a very important concept in biology today that leads to variations in genes. A mutation is a permanent alteration in the sequence of nitrogenous bases of a DNA molecule. The result of a mutation is generally a change in the end-product specified by that gene. In some cases, a mutation can be beneficial if a new metabolic activity arises in a microorganism, or it can be detrimental if a metabolic activity is lost. Mutations can be spontaneous, or induced by a mutagen in the environment. Mispairing is probably mostly due to cellular processes such as Tautomeric shift of bases , oxidative damage to DNA , Depurination and Deamination or caused by “environment”, i.e, chemicals, radiation, viruses, diet and lifestyle (Mutagens). Substitution of a nucleotide and Deletion or addition of them is two mechanisms of mutation. Mutation in bacteria has some results such as missense, nonsense, silent, frameshift, lethal, suppressor and conditional lethal mutation. Identifying these mutations requires detection methods. Classic methods i,e, Replica plating, Penicillin enrichment, Ames test, Use of chromogenic substrate and novel tests such as Polymerase chain reaction (PCR) and Gel electrophoresis, Gene probes and Southern blotting, DNA sequencing and DNA microarray are some of these methods that are highlighted in this review.